Efek Ketebalan Casing dan Ketebalan Media Terhadap Hasil Jamur Merang (Volvariella volvaceae) - A G Rosnina; Elvira Sari Dewi; Nanda Wahyudi (Faculty of Agriculture, Universitas Malikussaleh, 2017)
The mushroom in the Acehnese language is called the bowl/addy straw mushroom (Volvariella volvaceae) including the most well known fungi among several species of mushrooms cultivated in Indonesia. The purpose of this research is to study the effect of the thickness of the casing and the composition of the media on the yield of mushroom (Volvariella volvaceae) using a Factorial Randomized Design with three replications. The first factor is the composition of the media and the second factor is the thickness of the casing. Data analysis was done by using SAS V9.12 software and advanced test with Duncan test at 5% level. This experiment showed that there is a significant effect on the interaction between the treatment of the media composition and the thickness treatment of the casing (K1C1 and K0C1) on the head body weight per harvest period, and there is no interaction with other variables. While the composition of the media singularly significant effect on the length of the fruit body and the number of fruit body in the treatment of the composition of oil palm empty bunches + lime + bran + cornflour (K1). In other variables, although statistically not yet showing the difference, but on average it appears that the medium of oil palm empty bunches + lime + bran + cornflour (K1) has the frequency of harvest, fruit body diameter, fruit body length and total body weight and fruit weight is higher than the treatment others. While the average appearance of mushroom pin head of the highest value is in treatment (K0). Average treatment without casing (C0) in addition to affect the body length of the fruit (fruting body) also gives the highest value on the appearance of pin head (going to fruit body), harvest frequency, body diameter. While the appearance of the pin head, the number of fruit body and body weight of mushroom fruit perang has the highest value on the 5 cm thickness casing treatment (C1)